2022
DOI: 10.3389/fcell.2022.895178
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hematological Parameters Between First-Episode Schizophrenia and Anti-NMDAR Encephalitis

Abstract: Background: First-episode schizophrenia (FES) and anti-NMDAR encephalitis are different disorders with similar psychiatric symptoms, and both diseases are associated with the inflammatory system. In this study, we compared hematological parameters and inflammation ratios in anti-NMDAR encephalitis, FES, and healthy control.Methods: We enrolled 106 patients (53 FES patients and 53 anti-NMDAR encephalitis patients) and 59 healthy controls. The values of the neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…However, there were no differences in UCB levels between patients with schizophrenia and HCs in this study. On the contrary, in a recent study, Huang et al reported that there was no statistical difference in bilirubin levels between patients with first-episode schizophrenia and HCs [ 37 ]. Even more, some studies conducted in different countries (South Korea, China, and Norway) found varying degrees of reduction in serum bilirubin levels in patients with schizophrenia compared with HCs [ 21 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 94%
“…However, there were no differences in UCB levels between patients with schizophrenia and HCs in this study. On the contrary, in a recent study, Huang et al reported that there was no statistical difference in bilirubin levels between patients with first-episode schizophrenia and HCs [ 37 ]. Even more, some studies conducted in different countries (South Korea, China, and Norway) found varying degrees of reduction in serum bilirubin levels in patients with schizophrenia compared with HCs [ 21 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 94%